Return to play following COVID-19 infection-a systematic review of current evidence - Davey, M. S.; Davey, M. G.; Hurley, R.; Hurley, E. T.; Pauzenberger, L. (Journal of Sport Rehabilitation, 2022)
Context: The COVID-19 pandemic has had catastrophic impact on a global scale, affecting people from all walks of life including elite athletes. Objectives: The purpose of this study was to evaluate the reported rates of return to play (RTP) in conjunction with the expert-derived guidelines previously recommended to enable safe RTP post COVID-19 infection. Evidence Acquisition: Two independent reviewers searched the literature based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, utilizing the MEDLINE, Embase, and Scopus databases. Only studies that reported rates of RTP and/or recommended guidelines for safe RTP were included. Evidence Synthesis: Overall, 17 studies (3 level III and 14 level V) were included. A total of 3 studies reported rates of RTP in a total of 1255 athletes and 623 officials; 72 (30 symptomatic) were infected with COVID-19, 100% of whom were able to RTP post COVID-19 infection. Of the 14 studies recommending guidelines for safe RTP, 3 and 9 studies recommended 7 and 14 days of rest in isolation respectively for asymptomatic patients with COVID-19 infection, prior to safe RTP. In contrast, 7 studies recommended 3 to 6 months of rest (following 14 d isolation) in cases of COVID-19-induced myocarditis as a safe timeframe for safe RTP. Of the 11 studies reporting on whether blanket testing prior to RTP was recommended, only 7 studies recommended a negative test result as mandatory prior to RTP for athletes previously infected with COVID-19. Conclusions: Although excellent rates of RTP have been reported for elite athletes post COVID-19 infection, discrepancies in recommended rest periods, requirement for mandatory negative test results, and the magnitude of screening investigations required continue to exist in the literature, with a need for further standardized international guidelines required in future. Level of Evidence: Level V; systematic review of all forms of evidence.